1989
DOI: 10.1128/mcb.9.3.1233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of von Willebrand factor coexpression on the synthesis and secretion of factor VIII in Chinese hamster ovary cells.

Abstract: In plasma, antihemophilic factor (factor VIII) exists as a 200-kilodalton heavy-chain polypeptide in a metal ion association with an 80-kilodalton light-chain polypeptide. This complex is bound by hydrophobic and hydrophilic interactions to a large multimeric glycoprotein, von Willebrand factor (vWF). Accumulation of secreted human factor VIII activity expressed in Chinese hamster ovary cells requires the addition of serum in the growth medium, which provides vWF. Here we report that coexpression of vWF with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 65 publications
(55 reference statements)
1
112
0
1
Order By: Relevance
“…This represents the first demonstration of homologous expression of fVIII mRNA in primary cell culture. In contrast, previous studies of fVIII expression in cell culture have been conducted by transfecting fVIII gene fragments into liver cellderived cell lines (21,22) or Chinese hamster ovary cells (23,24). Our results should facilitate studies of fVIII gene regulation under more physiological conditions.…”
Section: Discussionmentioning
confidence: 47%
“…This represents the first demonstration of homologous expression of fVIII mRNA in primary cell culture. In contrast, previous studies of fVIII expression in cell culture have been conducted by transfecting fVIII gene fragments into liver cellderived cell lines (21,22) or Chinese hamster ovary cells (23,24). Our results should facilitate studies of fVIII gene regulation under more physiological conditions.…”
Section: Discussionmentioning
confidence: 47%
“…The development of gene transfer systems for treating haemophilia A have been hindered by the low expression of FVIII which is two orders of magnitude lower than for other proteins. 1 This is ascribed to the presence of transcriptional silencers within the FVIII cDNA [2][3][4] and inefficient intracellular transport and secretion of the protein. 5 The construction of retroviral vectors encoding FVIII has been especially problematic and is attributed to inefficient transcription of the vector genome.…”
Section: Introductionmentioning
confidence: 99%
“…Using a comparable retroviral vector delivery system, the levels of F.VIII produced in vitro were about 2 orders of magnitude lower than F.IX (218). The inefficiency of F.VIII production results from several factors, including inefficient expression of the mRNA, misfolding and degradation of the translated protein, and retention in the endoplasmic reticulum via binding to ER chaperones such as immunoglobulin binding protein (BiP) (218)(219)(220)(221)(222)(223)(224)(225).…”
Section: Additional Challenges In Hemophilia Amentioning
confidence: 99%
“…Studies in vitro have suggested that this stabilizing effect is enhanced when F.VIII and vWF are co-expressed in the same cell, rather than simply adding vWF to the media (219,228). However, while vWF is believed to be produced in endothelial cells, platelets, and megakaryocytes, the site of F.VIII synthesis is somewhat controversial (229)(230)(231).…”
Section: Additional Challenges In Hemophilia Amentioning
confidence: 99%